Incorporation of matte-slag thermochemistry into sulphide smelter discrete event simulation. (2nd January 2018) - Navarra, A.; Valenzuela, F.; Cruz, R.; Arrancibia, C.; Yañez, R.; Acuña, C.
ABSTRACT: Discrete event simulation (DES) is a suitable framework to evaluate and optimise the dynamics of sulphide smelters. In particular, iron–nickel–copper–cobalt sulphides undergo continual oxidation within a roasting or smelting operation, followed by batch oxidation within the converting operation, thus producing iron-free Bessemer matte (or blister copper, in the case of copper smelters); this semi-finished product undergoes further processing to produce nickel, copper and cobalt products, and to recover precious metals. The juncture between continuous smelting and batch converting is often an appropriate focus for the earliest phases of DES development, since it is typically a major bottleneck within nickel and copper smelters; later phases may include increasing levels of detail for auxiliary unit operations, as well as plant logistics. Moreover, DES can support matte-slag chemistry, including Gibbs free energy balances to determine the iron speciation within the slag. DES is therefore capable of linking the fundamentals of oxidation reactions to the intricacies of plant dynamics.